2019
DOI: 10.20452/pamw.15008
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the workup and management of Raynaud’s phenomenon

Abstract: oxide synthase 1 gene as significantly correlated with RP in the general population. 4 Major risk factors for primary RP include, in addition to the female sex and family history, a previous sensation of cold hands, migraine, cardiovascular diseases, decreased body mass index, manual occupation (not including vibration tool use), and estrogen replacement therapy. 3-6 Cigarette smoking and alcohol consumption are still of unclear significance when concerning the prevalence of primary RP. 7 Secondary RP associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
0
15
0
2
Order By: Relevance
“…Drug treatment is indicated when non-pharmacological interventions are insufficient to manage RP and is often required in patients with SRP (especially SSc). 47 Calcium channel blockers (eg nifedipine) are often used as first-line drug treatment for PRP and SRP. 8,33,48,49 Other drug classes which are used for the treatment of RP include angiotensin receptor II antagonists (eg losartan), angiotensin-converting enzyme (ACE) inhibitors, and selective serotonin receptor antagonists (eg fluoxetine).…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%
“…Drug treatment is indicated when non-pharmacological interventions are insufficient to manage RP and is often required in patients with SRP (especially SSc). 47 Calcium channel blockers (eg nifedipine) are often used as first-line drug treatment for PRP and SRP. 8,33,48,49 Other drug classes which are used for the treatment of RP include angiotensin receptor II antagonists (eg losartan), angiotensin-converting enzyme (ACE) inhibitors, and selective serotonin receptor antagonists (eg fluoxetine).…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%
“…Sympathectomy and amputation are advised as the extreme option in cases of irreversible tissue necrosis. Digital periarterial sympathectomy and endoscopic thoracic sympathectomy can be done in patients with refractory digital ischemia and severe complications [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with this limitation, more specific assessment of CTD-specific data (including nailfold videocapillaroscopy) was not feasible at that point. Therefore, other approaches for the diagnosis of RP, as previously suggested by others, were not deemed possible (33,35,36,37) Furthermore, the self-reported nature of the CTD questionnaire might lead to an overestimation of the prevalence of RP. However, the CTD questionnaire used in the current study had been previously validated, and was found to have a high sensitivity and specificity for screening large populations (7).…”
Section: 12mentioning
confidence: 99%